Kajian Yuridis Implementasi Otonomi Daerah dalam Pengembangan SDM Aparatur di Provinsi Lampung - Gresita Amalia Putri; Lucky Santoso; Hendra Irawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the implementation of regional autonomy in developing civil servant human resources in Lampung Province from a constitutional law perspective. It analyzes the extent to which regional authority is accompanied by institutional capacity strengthening in ASN management and identifies factors affecting its effectiveness. This research employs a normative juridical method using statutory and literature approaches. The findings indicate that regional autonomy implementation has not been fully supported by merit system optimization and institutional capacity strengthening, resulting in administrative-based rather than competency-based HR development. The regional government has implemented various training and competency development programs, yet these remain output-oriented rather than outcome-focused. Coordination among regional apparatus organizations remains suboptimal, creating policy fragmentation. Key obstacles include low technical competency of apparatus, bureaucratic mentality issues influenced by corruption, collusion, and nepotism practices, placement systems not fully based on merit, and limited budget allocation for training programs. This condition affects the effectiveness of public services at the local level. Strengthening the merit system, competency-based training, bureaucratic reform, and improved internal oversight are recommended to optimize regional autonomy implementation in Lampung Province.